2021
DOI: 10.1111/add.15378
|View full text |Cite
|
Sign up to set email alerts
|

Adapting treatment length to opioid‐dependent individuals’ needs and preferences: a 2‐year follow‐up to a 1‐year study of extended‐release naltrexone

Abstract: Background and aims Extended‐release naltrexone (XR‐NTX) is an under‐used treatment option for opioid dependence, today only available in a few countries in the world. Although effective, safe and feasible in short‐term treatment, long‐term data are scarce and there is no recommendation for required treatment length. The aims of the study were to determine the perceived need of long‐term XR‐NTX treatment and to examine long‐term treatment outcomes. Design In this prospective cohort study, following a parent 1‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(111 reference statements)
3
6
0
Order By: Relevance
“…However, experiences of satisfactorily reaching opioid abstinence after a few injections are in line with previous and current clinical observations of the phenomenon, and provide nuance to the understanding of early discontinuation of treatment as indicative of failed treatment (Dennis et al, 2020;Walker, 2009). It also supplements earlier findings from Solli et al (2020), who suggested that some XR-NTX patients might need longer than a year to reach their treatment goal. Findings from the current study suggest that for some, personal treatment goals may be achieved earlier than the framework of a clinical trial allows.…”
Section: Should Discontinuation Of Treatment Be Considered a Failure?supporting
confidence: 79%
See 1 more Smart Citation
“…However, experiences of satisfactorily reaching opioid abstinence after a few injections are in line with previous and current clinical observations of the phenomenon, and provide nuance to the understanding of early discontinuation of treatment as indicative of failed treatment (Dennis et al, 2020;Walker, 2009). It also supplements earlier findings from Solli et al (2020), who suggested that some XR-NTX patients might need longer than a year to reach their treatment goal. Findings from the current study suggest that for some, personal treatment goals may be achieved earlier than the framework of a clinical trial allows.…”
Section: Should Discontinuation Of Treatment Be Considered a Failure?supporting
confidence: 79%
“…Choosing to participate, despite the apprehension some expressed toward XR-NTX, might be understood as a last hope for help that would contribute to a better life (Jackson et al, 2003). However, many participants described not receiving adequate psychosocial support, which previous research has suggested can be a reason for discontinuation of treatment with XR-NTX (Solli et al, 2020). Studies have found that a supportive relationship with a therapist can predict significantly longer retention in outpatient treatment, often regardless of treatment type (Elliott et al, 2018;Hatcher & Barends, 1996;Jinks, 1999;Kasarabada et al, 2002;McLellan et al, 1988;Najavits et al, 2000;Redko et al, 2007).…”
Section: Unfulfilled Expectations Broken Hopes and Dreamsmentioning
confidence: 99%
“…A previous randomized controlled trial [ 2 ] demonstrated that XR-NTX is as safe and effective as buprenorphine-naloxone (an opioid agonist). The results were consistent with other studies [ 4 , 38 41 ], showing a decrease in opioid and substance use, improvements on psychosocial variables, and less opioid craving [ 3 , 42 44 ]. The need for XR-NTX to be reinforced by psychosocial interventions or psychological treatment [ 45 – 47 ] has been emphasized, while a lack of psycho-social follow-up has been linked to treatment discontinuation [ 44 ].…”
Section: Introductionsupporting
confidence: 92%
“…Access to OAT for large numbers of currently untreated people will be required. Similarly, access to evidence‐based treatments such as depot naltrexone [8, 9] will allow meeting the varied needs among OUD populations. Currently, in the United States, only approximately one‐third of those in need receive treatment [10].…”
mentioning
confidence: 99%